1991
DOI: 10.1002/1097-0142(19910615)67:12<3057::aid-cncr2820671221>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of androgen receptors in metastatic prostate cancer. Comparison of receptor content and response to hormonal therapy

Abstract: A longstanding goal has been to determine whether androgen receptor (AR) levels could be used to predict the clinical response of metastatic prostate cancer to androgen withdrawal therapy. A major limitation of previous studies was the use of homogenized tissue, which yields an average AR content for all cells. By AR immunohistochemical study using an antibody specific for AR the authors assessed nuclear AR content specifically in the malignant epithelial cells of prostate needle biopsy specimens of 17 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
1
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(106 citation statements)
references
References 24 publications
1
99
1
3
Order By: Relevance
“…Cancer cells which have lost their androgen receptors may acquire a growth advantage through the accumulation of several genetic changes. 20 Although some studies reported that the percentage of AR positive tumor cells did not correlate with the tumor grade or stage, 10 whereas others observed a significant correlation between AR immunostaining and histological grade. 6 In some reports, AR protein can be detected immunohistochemically in the majority of prostate cancer specimens which may contain mutations in the AR gene, however, in most samples it is not possible to determine the proportion of tumor cells expressing mutated AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells which have lost their androgen receptors may acquire a growth advantage through the accumulation of several genetic changes. 20 Although some studies reported that the percentage of AR positive tumor cells did not correlate with the tumor grade or stage, 10 whereas others observed a significant correlation between AR immunostaining and histological grade. 6 In some reports, AR protein can be detected immunohistochemically in the majority of prostate cancer specimens which may contain mutations in the AR gene, however, in most samples it is not possible to determine the proportion of tumor cells expressing mutated AR.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Several studies showed some prognostic significances of AR expression, 8,9 but others have failed to identify such a relationship. 10 In addition, some studies have demonstrated that a high variability in AR expression was presented within an individual tumor, in particular advanced prostate cancers. 11,12 Somatic mutations on the AR gene have been detected in human prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These data are in agreement with previous reports of AR-positive PC that is unresponsive to hormonal therapy. 14,15,16 Consequently, the percentage of AR-positive nuclei is not an absolute criterion for predicting response to hormonal therapy. 14 Various mechanisms can be proposed to explain unresponsive AR-positive PC , including some AR gene alterations, 17 which are not evident at the immunohistochemical level, although they can modify the functional status of ARs in malignant epithelial cells.…”
Section: Table 2 Hormonally Treated Prostatic Carcinomamentioning
confidence: 99%
“…AR is expressed throughout prostate cancer progression and its expression persists in the majority of patients with hormone-refractory disease (Cunha et al, 1987;Sadi et al, 1991;van der Kwast et al, 1991;Chodak et al, 1992;Hobisch et al, 1996;Mohler et al, 1996;Buchanan et al, 2001), and many AR mutations identified from hormone-refractory prostate tumors are capable of transactivation. These observations suggest that the eventual failure of ADT cannot be attributed simply to the loss of AR function.…”
Section: Introductionmentioning
confidence: 99%